Phages against Pathogenic Bacterial Biofilms and Biofilm-Based Infections: A Review - Siyu Liu; Hongyun Lu; Shengliang Zhang; Ying Shi; Qihe Chen (MDPI AG, 2022)
Bacterial biofilms formed by pathogens are known to be hundreds of times more resistant to antimicrobial agents than planktonic cells, making it extremely difficult to cure biofilm-based infections despite the use of antibiotics, which poses a serious threat to human health. Therefore, there is an urgent need to develop promising alternative antimicrobial therapies to reduce the burden of drug-resistant bacterial infections caused by biofilms. As natural enemies of bacteria, bacteriophages (phages) have the advantages of high specificity, safety and non-toxicity, and possess great potential in the defense and removal of pathogenic bacterial biofilms, which are considered to be alternatives to treat bacterial diseases. This work mainly reviews the composition, structure and formation process of bacterial biofilms, briefly discusses the interaction between phages and biofilms, and summarizes several strategies based on phages and their derivatives against biofilms and drug-resistant bacterial infections caused by biofilms, serving the purpose of developing novel, safe and effective treatment methods against biofilm-based infections and promoting the application of phages in maintaining human health.